Kompolnas as a Police Oversight Institution: A Constitutional Law and Human Rights Perspective - Putu Andika Wahyudi Putra; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the legal status and authority of Kompolnas within Indonesia’s constitutional law system and to evaluate the effectiveness of its role in protecting and ensuring the respect of human rights in police practices. The research employs normative legal methods with a conceptual approach. Primary, secondary, and tertiary legal materials were collected and analyzed using a descriptive-analytical method to understand Kompolnas’ position within the framework of constitutional law and human rights protection principles. The findings indicate that while Kompolnas holds a significant normative position as a manifestation of the principle of checks and balances in a constitutional state, its functional role remains weak because its authority is merely recommendatory. In terms of human rights protection, Kompolnas has yet to achieve full effectiveness, as its role appears more symbolic than substantive. The originality of this research lies in its integrative analysis combining constitutional law and human rights perspectives, emphasizing the necessity of regulatory reform to strengthen Kompolnas’ authority. These findings provide an important contribution to reinforcing external oversight of the police to ensure accountability and the protection of human rights.